2001
DOI: 10.1002/1521-3765(20011001)7:19<4164::aid-chem4164>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Influencing the Binding Selectivity of Self-Assembled Cyclodextrin Monolayers on Gold through Their Architecture

Abstract: Cyclodextrin derivatives modified with seven thioether moieties (1) or with one thiol moiety (2) bind to gold. Monolayers on gold of 1 or mixed monolayers of 2 and mercaptoundecanol were characterized by electrochemistry, wettability, and atomic force microscopy (AFM). Monolayers of 1 are well-ordered, but the order in the mixed monolayers depends on the ratio of 2 to mercaptoundecanol. With sufficient alkyl chains to fill the space under the cyclodextrin moiety of 2, the monolayers are densely packed. Guest r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
135
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(149 citation statements)
references
References 43 publications
14
135
0
Order By: Relevance
“…Figure 1 [32] Ferrocenemethanol gave a comparable binding constant of 9.9 10 3 m À1 , but with a less favorable DHA value of À6.1 kcal mol À1 and a more favorable TDSA value of À0.7 kcal mol À1 . [33] The large difference in DHA for BFc relative to Fc can be explained by the so-called "expanded hydrophobic surface", which has been proposed to explain trends observed for the inclusion of guests with an increasing number of aliphatic carbon atoms (N c ). [32] Dendrimer-b-CD assemblies: The apolar BFc dendrimers are virtually insoluble in water, but at pH 2 the addition of b-CD (b-CD/BFc = 10) resulted in soluble dendrimer-b-CD assemblies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 [32] Ferrocenemethanol gave a comparable binding constant of 9.9 10 3 m À1 , but with a less favorable DHA value of À6.1 kcal mol À1 and a more favorable TDSA value of À0.7 kcal mol À1 . [33] The large difference in DHA for BFc relative to Fc can be explained by the so-called "expanded hydrophobic surface", which has been proposed to explain trends observed for the inclusion of guests with an increasing number of aliphatic carbon atoms (N c ). [32] Dendrimer-b-CD assemblies: The apolar BFc dendrimers are virtually insoluble in water, but at pH 2 the addition of b-CD (b-CD/BFc = 10) resulted in soluble dendrimer-b-CD assemblies.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we showed that for small, monovalent guests the intrinsic binding constant at the surface K i,s is close to the intrinsic binding constant in solution K i,l . [39,40] To investigate if this also holds for BFc, titrations of 5 (aqueous solution at pH 12) against the b-CD SAM were performed and monitored by using SPR spectroscopy. Figure 4 shows the binding data and the fit to the Langmuir isotherm.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…14 A possible explanation for our observations considers that the inclusion of ferrocene units inside the cyclodextrin cavity is mainly controlled by a positive entropic change ( Sº) for the water molecules which, 1,35 upon inclusion, are transferred from the hydrophobic basket-like cavity (S (12) Comparison of equations 11 and 12 allows to predict that the stability constants K for the interfacial Fc CD complexes (see Table 2) must be lower 36 than those observed in solution, 14 . This condition holds when we note that the dielectric constants, H2O , for interfacial and bulk water regions (related to water structure rigidity or entropy), are 6 and 80 respectively.…”
Section: Binding Of CD With Fc Tethered To the Dendrimer Filmsmentioning
confidence: 99%
“…They have also been extensively used as chiral selectors in separation technology [18] and it has been shown that cyclodextrin based polymers could be used as sensitive layers in chiral sensing by SPR [16]. Reinhoudt has extensively studied the ability of these macrocycle to form well packed SAMs on gold surfaces [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%